2018
DOI: 10.4103/ijccm.ijccm_27_18
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting early treatment goals of sepsis patients presenting to the emergency department

Abstract: Background and Objectives:Sepsis is a major cause of emergency medicine admission. It is associated with high mortality and morbidity. Even though sepsis is common in the Indian subcontinent, there is a paucity of data on the management of sepsis in India. The aim was to study the factors affecting early treatment goals.Methods:All clinically suspected sepsis patients consenting to be part of the study were included. The diagnosis of sepsis was made by the treating physician in the emergency department as per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The prospective MOSAICS II study conducted at 386 ICUs across 22 Asian countries (including Vietnam) also showed that the overall prevalence of sepsis in ICUs was 22.4%, and the hospital mortality rate of sepsis was 32.6% [4]. It has been well documented that a delay in diagnosis and management of sepsis will cause an increase in mortality and morbidity [5]. Therefore, early detection and adequate treatment in the rst few hours after the development of sepsis can improve outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The prospective MOSAICS II study conducted at 386 ICUs across 22 Asian countries (including Vietnam) also showed that the overall prevalence of sepsis in ICUs was 22.4%, and the hospital mortality rate of sepsis was 32.6% [4]. It has been well documented that a delay in diagnosis and management of sepsis will cause an increase in mortality and morbidity [5]. Therefore, early detection and adequate treatment in the rst few hours after the development of sepsis can improve outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study from India found that 30% of patients with sepsis did not achieve early treatment goals due to various reasons including wrong triaging and physician's not recognizing sepsis. 7 The SIRS was introduced in 1991 in the international consensus guidelines to recognize sepsis, which was then replaced by qSOFA in 2016. 8 However, the diagnostic accuracy of both SIRS and qSOFA is suboptimal with modest sensitivities and specificities of 70% and 73% for qSOFA and 88% and 34% for SIRS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The prospective MOSAICS II study conducted at 386 ICUs across 22 Asian countries (including Vietnam) also showed that the overall prevalence of sepsis in ICUs was 22.4%, and the hospital mortality rate of sepsis was 32.6% [ 4 ]. It has been well documented that a delay in diagnosis and management of sepsis will cause an increase in mortality and morbidity [ 5 ]. Therefore, early detection and adequate treatment in the first few hours after the development of sepsis can improve outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%